Study of Gastropod Abundance and Diversity in Rajolelo Forest Park Bengkulu Province - Sayyida Khusnul Khotimah; Kasmiruddin; Mega Sari Apriniarti (Yayasan Darussalam Bengkulu, 2026)
Gastropods are a group of mollusks that play a crucial role in maintaining the balance of aquatic and terrestrial ecosystems through decomposition and as components of the food chain. This study aimed to analyze the diversity, abundance, dominance, and similarity of gastropod communities in the Rajolelo Grand Forest Park, Central Bengkulu. The study was conducted from November 2025 to January 2026 using the Visual Encounter Survey (VES) method combined with transects in two habitat types: an artificial lake and secondary forest. The data obtained were analyzed using the Shannon-Wiener diversity index, Simpson dominance index, relative abundance, and community similarity index. The results showed nine gastropod species from several families distributed across both study habitats. The artificial lake habitat had a higher number of individuals with certain species dominating, while the secondary forest habitat showed a more even community composition. These differences in community structure are related to habitat conditions, food source availability, and environmental factors such as temperature, pH, and humidity. In general, both habitats exhibit distinct yet complementary gastropod community characteristics in maintaining ecosystem balance in the Rajolelo Grand Forest Park area.